Investigação do processo oxidativo avançado (UVC/ H2O2/Carvão ativado) na eliminação de Ftalatos - Almeida, Maria Carolina de (2017)
The objective of this work was to compare the efficiency of conventional treatments such as activated carbon (AC) Adsorption and the advanced oxidation process (AOP), UV-C/H2O2, for degradation of diethyl phthalete (DEP) and coupling UV-C/H2O2/AC in laboratory effluent, ultrapure water and faucet water doped with DEP and laboratory effluent with multicomponents (DEP and phenol). The chemical characterization (Boehm method, pHPZC, IRTF, elemental analysis) and physical (volume of micropores and mesopores, mean micropore width by the Dubini-Radushkevich method were used as a predecessor to the kinetic adsorption study, Surface area and microporous specific volume by the alpha method, microporous and total surface, BET surface area by BET method, cumulative mesopore distribution and pore volume, cumulative area and surface area and pore size by BJH method) of AC. The factorial design with eleven tests and three independent variables (AC mass, temperature and pH) was applied, resulting in response surfaces for adsorption capacity, DEP elimination rate and equilibrium time without significant difference between the studied variables. Mathematical modeling of adsorption kinetics using the pseudo-first, pseudo-second order and intraparticle models was performed and the pseudo-second order model was fitted to the experimental kinetic adsorption data. It was followed by the study of the adsorption isotherms for the lower, intermediate and longer equilibrium experimental conditions. It was performed the mathematical modeling of the adsorption isotherms using the Langmuir and Freundlinch models, and adjusted to the Freundlinch model to the experimental data of the adsorption isotherms with higher determination coefficients (R2), confirming the predominant chemorandomization adsorption phenomenon. The treatment of AOP UV-C/H2O2 was then applied alone. The factorial design with eleven tests and three independent variables (H2O2 concentration, temperature and pH) was applied, resulting in surfaces of responses to DEP elimination rate with significant difference between the variables studied for pH, positive effect of H2O2 concentration (p < 0.5). The mathematical modeling of the kinetics of AOP using the first order models was carried out, and the kinetic experimental data of the photodegradation with high coefficients of determination (R2> 0.9) were fitted to the model. The degradation kinetics of DEP by AOP coupling and AC, UV-C/H2O2/AC were followed. The factorial design with eleven tests and three independent variables (H2O2 concentration, temperature and pH) and with 0.4 g of AC, resulting in surfaces of responses to elimination rate of DEP with significant difference between the variables studied for pH, positive effect of H2O2 concentration (p <0.5). The mass of AC was determined in 0.4 g for all eleven tests, because it was the mass applied at the highest rates of elimination of DEP by kinetics of Adsorption, which was confirmed by repeatability at the central points of the factorial design (C9, C10 and C11). The catalytic activity of the carbons for the Adsorption process in the presence of tertbutanol was high, however, after the determination of the kinetic parameters, the contribution was higher for photooxidation of DEP by the action of the AOP (homogeneous system).